Los hábitos alimenticios para mejorar el rendimiento escolar de los niños de primer grado paralelo “a” de la escuela de educación básica filomena mora de Carrión de la ciudad de Loja, periodo 2017-2018. - Moncayo Peña, Ana Elizabeth (2018)
This research work entitled: The alimentary habits to improve the school performance of children of first grade parallel "to" of the school of basic education Filomena Mora de Carrión of the city of Loja, period 2017-2018, has for general objective; improve the school performance of children of first grade parallel "A" of the School of Basic Education Filomena Mora de Carrión, of the city of Loja, period 2017-2018, with the practice of eating habits, the research is determined with a design of descriptive type, in addition to using the methods: scientific, deductive, analytical, statistical, to obtain the information, the survey technique was used, which was directed to the parents to know how these habits influence the education of their children; As an instrument, the "REAA" adaptation function test was applied to determine the children's school performance and the relationship of some of the areas evaluated with the feeding, which is obtained as the main result of the pre-test that 80% of the sample meets the areas of difficulty, then the proposal of activities was applied to children and parents in a period of two months and the evaluation was made with the post test, which shows a significant improvement of children in cognitive development, representing 67% with a good command in each of the areas, so it is concluded that the development and application of the proposal is essential to guide children and parents correctly and an adequate accompaniment to the teaching staff in the teaching-learning process, it is finally recommended that the teacher make work based on the plan that was executed, apply it daily in the s class to strengthen the developing areas of infants, this in order that there is no setback and obtain an integral development.